2015
DOI: 10.2466/22.24.pms.120v10x7
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Action Effects with Different Attention Foci is Reflected in Brain Activation

Abstract: Anticipation is informed by experience. Having focused on action effects in the past will lead to differences when the focus is now on the effector. Boules-type throwing movements were presented as point-light displays of shoulder and arm-markers. Activation in motor-related areas measured with functional magnetic resonance imaging was compared between two tasks: Task A anticipating action effects and Task B judging the velocity of the hand marker. One group of participants performed a session of Task A follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…One potential mechanism given for the process of anticipation is that the observer simulates the observed actions by using a predictive forward simulation which estimates the sensory effects of a movement. The prediction is suggested to be based on one’s movement experience and/or the observer’s own motor representations (see Bischoff et al, 2015 ). In a recent fMRI study, Bischoff and colleagues identified the core components of the anticipation network throughout an anticipatory task of boules’ throw ( Bischoff et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism given for the process of anticipation is that the observer simulates the observed actions by using a predictive forward simulation which estimates the sensory effects of a movement. The prediction is suggested to be based on one’s movement experience and/or the observer’s own motor representations (see Bischoff et al, 2015 ). In a recent fMRI study, Bischoff and colleagues identified the core components of the anticipation network throughout an anticipatory task of boules’ throw ( Bischoff et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In social interactions, humans demonstrate a remarkable ability to effortlessly understand and interpret the behavior and intention of others. With regard to this topic, it has been found that within this process the visual perception of human movements activates a complex cortical network that involves visual processing regions [ 1 3 ] as well as motor intention [ 4 , 5 ] or motor and somatosensory representations in the brain [ 6 13 ] which belong to the so-called mirror neuron system [ 14 ]. Direct electrophysiological recordings in monkeys [ 15 18 ] and humans [ 19 ] have shown a discharge in such mirror neurons during execution and perception of actions.…”
Section: Introductionmentioning
confidence: 99%